Predatory Mites (Acari: Phytoseiidae) in Agro-Ecosystems and Conservation Biological Control: A Review and Explorative Approach for Forecasting Plant-Predatory Mite Interactions and Mite Dispersal - Tixier, Marie-Stephane (Frontiers in Ecology and Evolution, 2018)
Phytoseiidae mites are efficient predators able to control pest mites and small arthropods in crops all over the world, using the three biological control strategies : (i) augmentation, (ii) classical and (iii) conservation. This paper focuses on this latter strategy. Most of those predatory mite species are generalist predators; they are naturally present in agro-ecosystems both on crops and adjacent natural vegetation. Because of such characteristics, their occurrence is usually associated to a lesser use of pesticides providing so ecosystem services. As a first baseline for managing their occurrence in agro-ecosystems, a review of the present knowledge of plants and predatory mite interactions and predator dispersal ability is proposed. In addition, based on the author own occurrence database, the study aims at analysing (i) plant traits and the potential co-evolutionary relationships between plants and predatory mite species and (ii) how this can be used for forecasting the plants favourable to key predatory mites. For this, some examples were taken, i.e. vine and citrus crops, and three species, Kampimodromus aberrans, Euseius stipulatus and Typhlodromus (Typhlodromus) pyri. The main conclusion is that the occurrence database can help in determining the probability to find some predatory mite species on crops and non crop plants. However, because some elements are lacking, especially predatory mite density, plant traits and real overall distribution, it is at that time and using the analyses presently carried out, difficult to associate plant traits and plant phylogeny to Phytoseiidae diversity. Additional meta-analyses in collaboration with plant specialists would be required. Finally, the paper presents some examples of agroecosystem management at different scales (intercropping, agroforestry, borders management, landscape).